VIRTUAL BORLIQ VA RAQAMLI MUHIT TUSHUNCHALARINING PEDAGOGIK MAZMUNI (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article analyzes the pedagogical essence of the concepts of virtual reality and digital environment, their role in modern education, didactic potential, and their impact on the development of students’ cognitive activity, independent thinking, and professional competencies. The study reveals educational transformations in the context of digitalization, virtual learning environments, blended and distance learning models, and the pedagogical capabilities of artificial intelligence and interactive technologies. The research substantiates the educational model of virtual reality, the concept of digital pedagogy, and its integration with learner-centered and competency-based approaches. The findings provide scientific and practical recommendations for the effective implementation of digital environments in educational institutions.